Risk factors for developing type 2 diabetes in homosexuals: A systematic literature review - Cortez-Beltran, Jose Guadalupe; Miranda-Félix, Patricia Enedina; Buichia-Sombra, Félix Gerardo; Ortiz-Félix, Rosario Edith (Horizonte Sanitario, 2022)
Objective: To identify the available scientific literature on risk factors for developing type 2 diabetes in homosexuals.Material and Methods: Scientific articles published between 2014 and 2020 in English and Spanish were searched in 5 electronic databases: Virtual Health Library, Google Scholar, Network of Scientific Journals from Latin America and the Caribbean, Spain and Portugal, Scientific Electronic Library Online and National Library of Medicine of the United States. Combinations were made with the Boolean logical descriptors and operators AND and OR: Obesity OR Diabetes AND Risk AND Homosexual, Diabetes AND Homosexual, Obesity AND Homosexual, Obesity AND Diabetes AND Homosexual, Risk AND Diabetes AND Obesity AND Homosexual according to Medical Subject Headings. To select the studies, the Joanna Briggs Institute Critical Appraisal tools guide in Spanish for analytical prevalence studies was followed.Results: Of 98 studies, 8 studies of United States origin and published in English were included. The sample of the studies ranged between 219 and 136 878 participants aged between 18 and 65 years. The available evidence suggests that the main risk factors for the development of type 2 diabetes in homosexuals are obesity, depression, stress, lack of health care, physical inactivity, tobacco and alcohol consumption, having prediabetes, high blood pressure, high Cholesterol levels and family history with type 2 diabetes.Conclusions: In conclusion, some of these risk factors are not considered by diabetes organizations, showing differences in the heterosexual population.Key Words: Risk factor; Risk; Type 2 diabetes; Homosexual.